2021
DOI: 10.1186/s12888-021-03500-y
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of brief dialectical behavior therapy skills training among borderline personality disorder patients in Malaysia: feasibility, acceptability, and preliminary outcomes

Abstract: Aim/background Even though dialectical behavior therapy (DBT) has received substantial empirical support in treating patients with borderline personality disorder (BPD), fewer studies have evaluated whether a brief DBT skills group may be effective in improving clinical outcomes in this population. Further, less is known regarding the feasibility and outcomes of DBT beyond Euro-American contexts. This paper describes outcomes from a pilot study examining the feasibility, acceptability, and clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Significant improvements in self-harm occurred in both treatment arms by 6 months and were sustained at 24-month follow-up (McMain et al, 2022). These results converge with a growing body of evidence which suggests that briefer forms of DBT for BPD are effective on a range of outcomes including self-harm (Keng et al, 2021;Westad, Hagen, Jonsbu, & Solem, 2021). By extension, lengthier treatments may not be necessary for all individuals with BPD (Griffiths et al, 2019).However, there is considerable heterogeneity in BPD treatment response; approximately half of BPD patients are considered non-responders following DBT and other BPD interventions (Woodbridge, Townsend, Reis, Singh, & Grenyer, 2022).…”
supporting
confidence: 56%
“…Significant improvements in self-harm occurred in both treatment arms by 6 months and were sustained at 24-month follow-up (McMain et al, 2022). These results converge with a growing body of evidence which suggests that briefer forms of DBT for BPD are effective on a range of outcomes including self-harm (Keng et al, 2021;Westad, Hagen, Jonsbu, & Solem, 2021). By extension, lengthier treatments may not be necessary for all individuals with BPD (Griffiths et al, 2019).However, there is considerable heterogeneity in BPD treatment response; approximately half of BPD patients are considered non-responders following DBT and other BPD interventions (Woodbridge, Townsend, Reis, Singh, & Grenyer, 2022).…”
supporting
confidence: 56%
“…This supports the idea (a) group DBT offers something more than generic group effects (which the placebo phase controls for), (b) the skills development content in group DBT is important for clients, and effective when administered online (Gutteling et al ., 2012), and (c) DBT procedures addressed primarily emotional regulation processes (Barney et al ., 2019; Goodman et al ., 2014). Two things are especially notable: (a) a marked difference in clients’ emotional dysregulation when receiving individual plus group DBT sessions but not when group placebo was added to individual therapy and (b) changes in emotional dysregulation associated with a brief 8-week DBT online group compared with the usual length of group DBT (Heerebrand et al ., 2021; Keng et al ., 2021; Safer et al ., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Keng et al . (2021) found that a 14-week program produced significant reductions in depression and emotion-regulation in adults with BPD, and non-significant reductions in self-harm, suicidal ideation and anxiety. Zapolski and Smith (2017) found mixed results in a brief (9-week) DBT skills group for adolescents, finding a significant decrease in intent to engage in risky behaviours, but no significant changes in negative mood.…”
Section: Introductionmentioning
confidence: 99%
“…Acceptability is often measured through a combination of simple quantitative scales, and qualitative feedback. This method has previously been utilised by pilot programs in the treatment of people with BPD (e.g., [ 54 , 55 ]). In the current study, program acceptability was assessed through online survey evaluation questions at completion.…”
Section: Methodsmentioning
confidence: 99%